2017
DOI: 10.1186/s12985-017-0735-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of mosaic recombinant strains potentially associated with vaccine JXA1-R and predominant circulating strains of porcine reproductive and respiratory syndrome virus in different provinces of China

Abstract: BackgroundPorcine reproductive and respiratory syndrome virus (PRRSV) has caused several outbreaks in China since 2006. However, the genetic diversity of PRRSV in China has greatly increased by rapid evolution or recombination events. Modified live-attenuated vaccines are widely used to control this disease worldwide. Although the risk and inefficacy of the vaccine has been reported, the genetic diversity between epidemic field strains and vaccine strains in China has not been completely elucidated.MethodsA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Recombination between PRRSV field strains has been extensively described for PRRSV-2 (Dong et al, 2017;Li et al, 2009;Wenhui et al, 2012;Zhao et al, 2017) and less frequently for PRRSV-1 (Dortmans, Buter, Dijkman, Houben, & Duinhof, 2019;Martin-Valls et al, 2014). More rarely, recombination between PRRSV-1 field strains and strains of PRRSV-1 MLV vaccine strains has been reported (Chen et al, 2017;Frossard et al, 2013;Marton et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…Recombination between PRRSV field strains has been extensively described for PRRSV-2 (Dong et al, 2017;Li et al, 2009;Wenhui et al, 2012;Zhao et al, 2017) and less frequently for PRRSV-1 (Dortmans, Buter, Dijkman, Houben, & Duinhof, 2019;Martin-Valls et al, 2014). More rarely, recombination between PRRSV-1 field strains and strains of PRRSV-1 MLV vaccine strains has been reported (Chen et al, 2017;Frossard et al, 2013;Marton et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, genovariations of PRRSVs have been frequently observed. Recently, several provinces in China reported outbreaks of NADC30-like PRRSVs with genovariations existing in the open reading frame 5 (ORF5) region of the genome of PRRSVs ( 2 , 3 , 7 11 ). Herein, we report the full-length genome sequence and molecular characteristics of a novel subgenotype of the PRRSV strain JX/CH/2016 isolated in Jiangxi, China.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Recently, QYYZ-like PRRSV strains were discovered to recombine with JXA1-like strains (GDsg and GD1404) [ 15 , 16 ]. Additionally, NADC30-like strains were found to recombine with JXA1-like strains (HENAN-HEB, JL580, FJ1402, TJnh1501, 15HEN1, HNhx, and SCnj16) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] or VR-2332-like strains (Chsx1401, HENAN-XINX, and HNyc15) [ 14 , 20 , 24 ]. Moreover, several complex recombinants among the three lineages of PRRSV-2 strains (SDhz1512, SD17-38, SCcd16, SCcd17, and SCya17) have also been observed in China [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that natural recombination can occur between PRRSV field strains as well as between field and modified live virus (MLV) vaccine strains [ 22 , 29 , 30 ]. Since the highly pathogenic PRRS (HP-PRRS) outbreaks in China in 2006 [ 31 ], imported and domestic commercial MLV vaccines, such as CH-1R (parental strain CH-1a), Ingelvac PRRS MLV/RespPRRS MLV (VR-2332), JXA1-P80 (JXA1), TJM-F92 (TJ), HuN4-F112 (HuN4), R98 (R98), and GDr180 (GD), have been used to safeguard against PRRSV-2 throughout the country.…”
Section: Introductionmentioning
confidence: 99%